Clinical and Social Variables Association on the Frequency of Intellectual Disability Persons to Dental Care - Francielle Ribeiro Alves; Victor Pinheiro Gavina; Nayara Silva Alves; Flavia Maia Silveira; Karine Laura Cortellazzi; Andréa Videira Assaf (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the association of oral health indicators and social variables on the frequency of visit to the dentist by persons with intellectual disability (ID). Material and Methods: The study comprised a sample consisting of 149 participants with ID, aged from 11 to 29 years, from non-governmental institutions. Semi-structured interviews were held to collect sociodemographic and psychosocial information with their parents/guardians, followed by oral health evaluations in accordance with World Health Organization criteria. Crude analyses and multiple analysis were conducted to test whether oral health indicators and social data were predictors of the visit to dental care services. Results: In the multiple logistic regression model, individuals with lower DMF-t (OR=3.13; 95% CI=1.40-6.97) and those with less crowded housing (OR=2.33; 95% CI=1.06-5.12) presented less frequency of visits to oral health services. Conclusion: DMFT and crowded housing are associated to the frequency of persons with intellectual disability to dental care as well as this outcome measure affects the oral health of persons with ID. Therefore, identifying limiting factors to dental care of persons with intellectual disability is needed so that this group can receive adequate attention.